Advances in shock timing experiments on the National Ignition Facility. (March 2016) - Robey, H F; Celliers, P M; Moody, J D; Sater, J; Parham, T; Kozioziemski, B; Dylla- Spears, R; Ross, J S; LePape, S; Ralph, J E; Hohenberger, M; Dewald, E L; et al.
Abstract: Recent advances in shock timing experiments and analysis techniques now enable shock measurements to be performed in cryogenic deuterium-tritium (DT) ice layered capsule implosions on the National Ignition Facility (NIF). Previous measurements of shock timing in inertial confinement fusion (ICF) implosions were performed in surrogate targets, where the solid DT ice shell and central DT gas were replaced with a continuous liquid deuterium (D2) fill. These previous experiments pose two surrogacy issues: a material surrogacy due to the difference of species (D2 vs. DT) and densities of the materials used and a geometric surrogacy due to presence of an additional interface (ice/gas) previously absent in the liquid-filled targets. This report presents experimental data and a new analysis method for validating the assumptions underlying this surrogate technique.